Characterization of Visual Symptomatology Associated with Refractive, Accommodative, and Binocular Anomalies - Pilar Cacho-Martínez; Mario Cantó-Cerdán; Stela Carbonell-Bonete; Ángel García-Muñoz (Journal of Ophthalmology)
Purpose. To characterize the symptomatology of refractive, accommodative, and nonstrabismic binocular dysfunctions and to assess the association between dysfunctions and symptoms. Methods. 175 randomised university students were examined. Subjects were given a subjective visual examination with accommodative and binocular tests, evaluating their symptomatology. Accommodative and binocular dysfunctions (AD, BD) were diagnosed according to the number of existing clinical signs: suspect AD or BD (one fundamental clinical sign), high suspect (one fundamental + 1 complementary clinical sign), and definite (one fundamental + 2 or more complementary clinical signs). A logistic regression was conducted in order to determine whether there was an association between dysfunctions and symptoms. Results. 78 subjects (44.6%) reported any kind of symptoms which were grouped into 18 categories, with “visual fatigue” being the most frequent (20% of the overall complaints). Logistic regression adjusted by the presence of an uncorrected refractive error showed no association between any grade of AD and symptoms. Subjects with BD had more likelihood of having symptoms than without dysfunction group (OR = 3.35), being greater when only definite BD were considered (OR = 8.79). Conclusions. An uncorrected refractive error is a confusion factor when considering AD symptomatology. For BD, the more the number of clinical signs used the greater the likelihood suffering symptoms.